To solve the quadratic equation 2c^2 + 5c + 3 = 0 using the factorization method, we need to factorize the quadratic expression and set each factor equal to zero.
Given equation: 2c^2 + 5c + 3 = 0
To factorize this quadratic expression, we need to find two numbers whose product is 2 * 3 = 6 and whose sum is 5.
The numbers that fulfill these conditions are 2 and 3.
So we can rewrite the equation as follows by splitting the middle term:
2c^2 + 2c + 3c + 3 = 0
Now, factor by grouping:
(2c^2 + 2c) + (3c + 3) = 0
Take out the common factors:
2c(c + 1) + 3(c + 1) = 0
Notice that we have a common factor of (c + 1), so we can simplify further:
(2c + 3)(c + 1) = 0
We set each factor equal to zero:
2c + 3 = 0 or c + 1 = 0
Solving for c in each equation:
2c = -3 or c = -1
Dividing both sides of the first equation by 2:
c = -3/2
Thus, the solutions to the quadratic equation 2c^2 + 5c + 3 = 0 are c = -3/2 and c = -1.
Solve the quadratic equation using factorisation method:2c^2+5c+3=0
1 answer